Deep ocean mineral water accelerates recovery from physical fatigue - Hou, Chien-Wen (BioMed Central, 2013)
BACKGROUND: Deep oceans have been suggested as a possible site where the origin of life occurred. Along with this theoretical lineage, experiments using components from deep ocean water to recreate life is underway. Here, we propose that if terrestrial organisms indeed evolved from deep oceans, supply of deep ocean mineral water (DOM) to humans, as a land creature, may replenish loss of molecular complexity associated with evolutionary sea-to-land migration. METHODS: We conducted a randomized, double-blind, placebo-controlled crossover human study to evaluate the effect of DOM, taken from a depth of 662 meters off the coast of Hualien, Taiwan, on time of recovery from a fatiguing exercise conducted at 30°C. RESULTS: The fatiguing exercise protocol caused a protracted reduction in aerobic power (reduced VO(2max)) for 48 h. However, DOM supplementation resulted in complete recovery of aerobic power within 4 h (P < 0.05). Muscle power was also elevated above placebo levels within 24 h of recovery (P < 0.05). Increased circulating creatine kinase (CK) and myoglobin, indicatives of exercise-induced muscle damage, were completely eliminated by DOM (P < 0.05) in parallel with attenuated oxidative damage (P < 0.05). CONCLUSION: Our results provide compelling evidence that DOM contains soluble elements, which can increase human recovery following an exhaustive physical challenge.